Influence of the Paracoccidioides brasiliensis 14-3-3 and gp43 proteins on the induction of apoptosis in A549 epithelial cells - Silva, Julhiany de Fatima da [UNESP]; Vicentim, Juliana [UNESP]; Oliveira, Haroldo Cesar de [UNESP]; Marcos, Caroline Maria [UNESP]; Assato, Patricia Akemi [UNESP]; Andreotti, Patricia Ferrari [UNESP]; Monteiro da Silva, Juliana Leal [UNESP]; Soares, Christiane Pienna [UNESP]; Benard, Gil; Fusco Almeida, Ana Marisa [UNESP]; Mendes-Giannini, Maria José Soares [UNESP] (Fundaco Oswaldo Cruz, 2015)
The fungal strain Paracoccidioides brasiliensis remains viable inside of epithelial cells and can induce apoptosis in this population. However, until now, the molecules that participate in this process remained unknown. Thus, this study evaluated the contribution of two P. brasiliensis molecules, the 14-3-3 and glycoprotein of 43 kDa proteins, which had been previously described as extracellular matrix adhesins and apoptosis inductors in human pneumocytes. Accordingly, epithelial cells were treated with these molecules for different periods of time and the expression of the apoptosis regulating-proteins Bak, Bax, Bcl-2, p53 and caspases were evaluated by terminal deoxynucleotidyl transferase dUTP nick end labelling, flow cytometry and real-time polymerase chain reaction analysis. Our results demonstrated that treatment with these molecules induces apoptosis signalling in pulmonary epithelial cells, showing the same pattern of programmed cell-death as that observed during infection with P. brasiliensis. Thus, we could conclude that P. brasiliensis uses these molecules as virulence factors that participate not only in the fungal adhesion process to host cells, but also in other important cellular mechanisms such as apoptosis.
Keywords: Paracoccidioides brasiliensis; Adhesins; Apoptosis